1971
DOI: 10.1104/pp.47.4.562
|View full text |Cite
|
Sign up to set email alerts
|

Kinetin and Carbohydrate Metabolism in Chinese Cabbage

Abstract: The effects of kinetin on starch and sugar levels and on 4CO2 and aP-orthophosphate labeling patterns of floated Chinese cabbage (Brassica pekinensis) leaf discs were investigated. Kinetin caused gross starch degradation. Neutral sugars were depressed by 30 to 40% in leaf tissue treated with kinetin for 24 hours. 14CO2 labeling of leaf discs pretreated with kinetin for 24 hours showed increased radioactivity in chloroform-soluble material and most sugar phosphates, and a 35 to 40% decrease in radioactivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…8 b) kinetin treatments exhibited an analogous picture as those of the first stage. Such findings could agree with those of ERISMANN and FRANHAUSER (1967), BERRIDGE and RALPH (1971) and LUSTINEC et al (1974) who found excessive accumulation of starch in treated plants. Moreover, DEZSI and FRANKS (1968), 8S KHALIL and MANDURAH HEGAZV et al (1972) and ZERBE and WILD (1980) reported increase in reducing sugars and sucrose content of barley, beans and Sinapis alba.…”
Section: Carbohydrate Content: Data Illustrated Insupporting
confidence: 92%
“…8 b) kinetin treatments exhibited an analogous picture as those of the first stage. Such findings could agree with those of ERISMANN and FRANHAUSER (1967), BERRIDGE and RALPH (1971) and LUSTINEC et al (1974) who found excessive accumulation of starch in treated plants. Moreover, DEZSI and FRANKS (1968), 8S KHALIL and MANDURAH HEGAZV et al (1972) and ZERBE and WILD (1980) reported increase in reducing sugars and sucrose content of barley, beans and Sinapis alba.…”
Section: Carbohydrate Content: Data Illustrated Insupporting
confidence: 92%
“…5). Berridge and Ralph (3) reported that kinetin induced starch degradation and increased the flow of sugars into lipids and structural materials in floating cabbage leaf discs. This result may mean that the nutrition of BA-treated detached wheat leaf tissue was directed towards the synthesis of cellular structural components.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on growth is associated, at least in some cases, with an accelerated mobilization of starch reserves (1,9,10). We have recently observed that BA also accelerates the disappearance of reserve fat in excised sunflower cotyledons (O. Servettaz and C. P. Longo, unpublished data).…”
mentioning
confidence: 99%